A simple technical innovation to prevent needle stick injuries among dental professionals - Tabassum, N.; Rida Dimashkieh, M.; Chowdary Jasthi, V.; Murdhi Alenazi, F.; Mohamed Mostafa Kamal, A.; Kumar, S. M.; Qerban, A. A.L.; Mohidin Demachkia, A. [UNESP]; Al Salem, A.; Swapna Lingam, A.; Khalid Faisal Alfirm, G.; Ahmed, S.; et al. (My University, 2024)
OBJECTIVE: Dental healthcare personnel face the potential danger of being exposed to infectious patients while administering local anesthesia injections during dental operations. This could lead to unintentional transfer of infectious diseases from patients to physicians. Although safety measures such as the One-hand-scoop technique and the use of safety syringes, plastic needle cap holders, and needles with safety caps are in place, there have been instances of needle stick injuries reported in clinics. This might be due to the lack of adherence to conventional safety measures or the impracticality of safety techniques and safety syringes. This article aims to demonstrate the utilization of dental tweezers, specifically London College tweezers or dental forceps, for the secure recapping of needles, eliminating the requirement for extra equipment or devices. SUBJECTS AND METHODS: After obtaining ethical approval (Approval No.: 024-01-2024) from the College of Dentistry, Dar Al Uloom University, 67 dental professionals, with consent for participation in the study, were included. They were requested to use dental tweezers/London College tweezers and dental extraction forceps such as maxillary anterior, mandibular anterior, and maxillary bayonet root forceps individually to recap the local anesthetic needles. The efficacy of these techniques was evaluated against the one-hand scoop technique for its ease, convenience, and reliability in preventing needle stick injuries. RESULTS: The evaluation of dental professionals regarding the ease of using dental tweezers to recap needles, compared to the one-hand scoop technique (p=0.592), maxillary bayonet root forceps (p=0.746), mandibular anterior forceps (p=0.380), and maxillary anterior forceps (p=0.808), did not yield statistically significant results. The assessment of the procedural simplicity of the one-hand scoop technique showed a satisfaction rate of over 40%, whereas the application of dental tweezers resulted in a satisfaction rate of 30%. However, the use of dental tweezers for needle recapping resulted in a satisfaction rate of over 50%, compared to a satisfaction rate of 30% for the one-handed scoop technique. CONCLUSIONS: There is no statistically significant difference in the assessment of the efficacy of dental tweezers and the one-hand scoop technique, bayonet root forceps, mandibular anteri- or forceps, maxillary anterior forceps, and dental tweezers for the needle capping technique. Therefore, dental forceps can be used instead of the one-handed scoop approach. The needle recapping procedure outlined in our study, aimed at preventing needle stick injuries, is simple to implement, and all dental specialties have convenient access to the required instruments.
Keywords: Dental extraction; Dental forceps; Infectious diseases; Needle stick injuries; Safety needles; Sharps injuries; Syringes